Factors that Impact Countries’ Innovation in Computer Science Research Publications - Nazik Alturki, Evon Abu-Taieh,; Hebah Nasereddin, Auhood AlFares, (Opción)
This paper has four primary goals. First, to examine the number of Computer Science documents published from of 1996 to 2017, which has shown the rise and fall of some countries. Second, to examine differences between countries, using a gap analysis, to enable a country classification to be introduced according to each country’s’ computer science documents published in 2017. Third, the study sought to examine the factors affecting the number of computer science documents published in 2017. Fourth, this paper discusses China and India’s means and methods to increase their computer science publication reflected in eight methods and means